Effect of an Adjustable Hinged Operating Table on Lumbar Lordosis During Lumbar Surgery. Issue 4 (15th February 2018) - Sebastian, Arjun S.; Ahmed, Amin; Vernon, Brian; Nguyen, Emily C.; Aleem, Ilyas; Clarke, Michelle J.; Currier, Bradford L.; Anderson, Paul; Bydon, Mohamad; Nassr, Ahmad
Abstract : Study Design: Prospective observational study. Objectives: Quantify the amount of lumbar lordosis achieved on a hinged operative table in neutral, flexion, and extension. Summary of Background Data: Hinged operative tables may allow surgeons to adjust lumbar spine positioning intraoperatively. The amount of lumbar lordosis in neutral, flexion, and extension positions has not been quantified prospectively using a hinged table. Methods: Thirty patients undergoing elective lumbar surgery were enrolled. Standing x-rays taken in neutral, maximal flexion, and maximal extension were obtained. After prone positioning on a hinged operative table, x-rays in neutral, maximal flexion, and maximal extension were taken. Total lumbar lordosis was calculated for all six images by two physicians. Disc degeneration was graded using Pfirrmann grades. Results: Lumbar lordosis on the operative table was 56.5 °  ± 2.1 °, 43.6 °  ± 2.2 °, 63.2 °  ± 2.0 ° compared with 46.9 °  ± 3.1 °, 33.2 °  ± 2.8 °, 52.3 °  ± 3.3 ° on the standing films in neutral, flexion, and extension, respectively. Average flexion (12.9 °  ± 1.1 ° ) and extension (6.7 °  ± 1.2 ° ) were significantly different from neutral on the table ( P  < 0.001). Lumbar lordosis was significantly higher on the operative table ( P  < 0.001). Total range of motion was 19.6 °  ± 1.9 ° on the table and 19.1 °  ± 2.0 ° with standing ( P  = 0.42). Average Pfirrmann disc grade was 2.77 ± 0.10 that did not correlate with range of motion ( P  = 0.40). Conclusion: In this cohort, the hinged operative table allowed for a physiologic arc of motion of nearly 20 ° from flexion to extension. A considerable amount of lumbar sagittal motion can be obtained on hinged operative tables without decreasing overall lumbar lordosis below physiologic levels. Level of Evidence: 3